Rock music styles a history - Charlton, Katherine (Boston McGraw-Hill, 2008)
Ragtime, tin pan alley, and jazz roots of rock; The blues and rhythm and blues roots of rock; Gospel and country roots of rock; Early rock and roll; Teen-styled rock music; Soul and motown; The British invasion: the Beatles versus the stones; The British invasion continues and America reacts; Folk, folk-rock, and singer/songwriters...
Includes index
Keywords: Rock music -- History and criticism; Nhạc Rock